2022
DOI: 10.3390/foods11172648
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Ultrasound Processing Enhances the Bioactive Compounds, Antioxidant Capacity and Microbiological Quality of Melon (Cucumis melo) Juice

Abstract: The bioactive compounds, antioxidant capacity and microbiological quality of melon juice processed by high-intensity ultrasound (HIUS) were studied. Melon juice was processed at two ultrasound intensities (27 and 52 W/cm2) for two different processing times (10 and 30 min) using two duty cycles (30 and 75%). Unprocessed juice was taken as a control. Total carotenoids and total phenolic compounds (TPC) were the bioactive compounds analyzed while the antioxidant capacity was determined by DPPH, ABTS and FRAP ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Rodrigues-Rico et al (2022) applied thermal pasteurization and ultrasound treatments to fresh melon juice (DPPH: 29 %). DPPH levels reached 39 % and 46 %, respectively [51] . The observed increase in antioxidant activity in our study, as well as in other research findings, could be attributed to the heightened activity of phenolic compounds and acids, which act as potent free radical scavengers during ultrasound treatment [52] .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Rodrigues-Rico et al (2022) applied thermal pasteurization and ultrasound treatments to fresh melon juice (DPPH: 29 %). DPPH levels reached 39 % and 46 %, respectively [51] . The observed increase in antioxidant activity in our study, as well as in other research findings, could be attributed to the heightened activity of phenolic compounds and acids, which act as potent free radical scavengers during ultrasound treatment [52] .…”
Section: Resultsmentioning
confidence: 96%
“…4 ). Rodríguez-Rico et al [51] showed that 10–15 min of ultrasound treatment at 10 ± 2℃ applied to melon juice in 2022 caused an increase in color score by minimizing the color change compared to the control and in the heat treatment investigation carried out by Lepaus et al [65] involving an orange-carrot juice blend, the samples treated for 30 s at 90 ℃ yielded scores of 6.79 ± 1.82 compared to the control sample, which achieved a general acceptability score of 7.64 ± 1.39. On the contrary, the ratings for samples treated with ultrasound for 5 and 10 min at 60 °C were 6.24 ± 2.28 and 4.72 ± 1.87, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, among them there was no significant difference. The effect of the HIUS treatment also caused color change in the melon juices [23] and kiwi [24], which may be related to the oxidation reaction (depending on the treatment time) and/or variation in the concentration of compounds due to sonication.…”
Section: Physicochemical Characterizationmentioning
confidence: 99%
“…Observing the signals of the major compounds, it is noted that in the HT sample that underwent heating only, without the aid of ultrasound, the signals decreased a little. In a study to monitor the quality of orange juice, it was found that heat-treated samples lost their turbidity and had their ascorbic acid content reduced by 7% [30], while high-intensity ultrasound processing enhanced the bioactive compounds on melon juice [23].…”
Section: H Nmr and Hplc-dad Analysismentioning
confidence: 99%
See 1 more Smart Citation